Tax enforcement and R&D credits - Cowx, Mary (Journal of Accounting and Economics, 2025)
Tax enforcement deters noncompliance, increasing tax revenue, but may also discourage taxpayer investment in activities that policymakers aim to incentivize through tax credits and deductions. This paper investigates this investment-revenue trade-off through the lens of the research and development (R&D) tax credit, a federal tax incentive that is highly scrutinized by the Internal Revenue Service (IRS). My results suggest that expectations about IRS corporate tax scrutiny are negatively associated with both R&D tax credits and R&D investment, on average. I estimate each $1 of aggregate enforcement spending is associated with a reduction in R&D tax credits of $2.64. In terms of elasticities, a 1 % increase in my estimate of IRS corporate tax scrutiny is associated with a decline in R&D tax credits and R&D investment of 0.4 % and 0.2 %, respectively. A survey of 116 managers further supports that the risk of IRS scrutiny affects both R&D tax credit take-up and R&D investment decisions. Moreover, both the survey responses and archival evidence underscore the importance of internal information quality in claiming R&D tax credits, suggesting tax policy simplification as a means to address enforcement-related declines in R&D investment.